Genetic diversity among reptilian orthoreoviruses isolated from pet snakes and lizards - Varga-Kugler, Renáta; Ihász, Katalin; Marton, Szilvia; Kaszab, Eszter; Marschang, Rachel E.; Farkas, Szilvia; Bányai, Krisztián (Frontiers in Veterinary Science, 2023)
Reovirus infections in reptiles are frequently detected and associated with various clinical diseases; yet, our knowledge about their genetic diversity and evolutionary relationships remains limited. In this study, we characterize at the genomic level five reptile origin orthoreovirus strains isolated from exotic snakes and lizards in Hungary and Germany. The genomic organization of the study strains was similar to that of the representative strains of reptile origin reoviruses belonging to species Reptilian orthoreovirus and Testudine orthoreovirus. Additionally, all five study strains clustered with the bush viper origin reference Reptilian orthoreovirus strain, 47/02. The nucleotide sequence divergence among strains fell from 56.64% to 99.36%. Based on genome segment constellations two well separated groups were observed, which may represent two genetic lineages of reptilian orthoreoviruses we tentatively referred here as genogroups, classifying two squamata origin strains with available whole genome sequences into genogroup I (GGI) and four strains into genogroup II (GGII). The representative GGI and GGII reptilian orthoreovirus strains are characterized by moderate-to-high nucleotide and amino acid similarities within genogroups (range, 69.45% to 99.36% and 74.64% to 100.00%), whereas lower nucleotide and amino acid similarities (range, 56.64% to 77.24% and 54.53% to 93.85%) and different structures of the bicistronic S1 segment were found between genogroups. Further studies are needed to explore the genomic diversity among reptilian reoviruses of squamata origin; this would be critical to establish a robust classification system for these viruses and to see if interaction among members of distinct lineages may result in viable progenies with novel genetic features.